Information and communication technologies for the poor - Torero, Máximo; von Braun, Joachim (International Food Policy Research Institute, 2005)
This brief is based on Information and Communication Technologies for Development and Poverty Reduction: The Potential of Telecommunications, ed. Maximo Torero and Joachim von Braun (Johns Hopkins University Press and IFPRI, 2006) "The variety of views about ICTs reveals that their role in development is unclear, especially without convincing evidence of their impact—and little research has been conducted on the direct and indirect links between ICTs and poverty reduction. A new book, Information and Communication Technologies for Development and Poverty Reduction: The Potential of Telecommunications, published by the Johns Hopkins University Press for IFPRI, addresses several pressing questions surrounding ICTs. How do ICTs affect economic development in low-income countries? How do they affect poor people in these countries and in rural areas in particular? What policies and programs facilitate their potential to enhance development and the inclusion of poor constituents? The book presents researchers’ findings related to five critical questions. (1) What link exists between ICT growth and economic growth? (2) Do weak institutions block effective use of ICTs? (3) Have ICTs been adapted to low-income countries, and have they had an impact on SMEs? (4) Does household access to ICTs remain constrained? (5) Can ICTs play a role in providing pro-poor public goods and services?